Teaching theory: A multilevel framework for systematic and engaged learning and teaching processes and successful outcomes - Raza , Muhammad Hassan (American Journal of Education and Learning, 2025)
The purpose of this paper is to present teaching theory, its three components- assumptions, concepts, and propositions, and its application in higher education classrooms. A post-test evaluation design was used to assess the effectiveness of teaching theory. Qualitative data were collected through a classroom survey from undergraduate and graduate level classes including online and seated classes to investigate the application of teaching theory. The results showed that learning and teaching outcomes were improved when learning and teaching were implemented at three different engagement levels (i.e., learner level, peer level and classroom level). Students and teachers’ engagement increased when teaching theory was operationalized and implemented in classrooms. Additionally, it was essential to consider and implement developmental, sociocultural and need-based contexts to foster learning and teaching at the three engagement levels of teaching theory. Students and teachers’ proactiveness, sensitivity and responsiveness were important factors in carrying out a successful learning and teaching process. In sum, teaching theory substantially improved learning and teaching outcomes in higher education classrooms. Teaching theory facilitates students and teachers in all types of classrooms at all educational levels and with all groups of the population for achieving positive educational outcomes.